APLICATION OF ETHYLENE ABSORBEN PACKAGING ON GUAVA (Psidium guajava L.) STORAGE - Dwi Dian Novita (The University of Lampung, 2015)
Ethylene production of guava fruit (Psidiumguajava L.) increased in ripening phase. Tomaintain the quality offruit so the ethylene should be reduced fromstorage roomto inhibited respiration rate. The aims of this researchwere: (1) to find out the effect of KMnO4 against guava shelflife based on weight lose, hardness, soluble solidcontent, and vitaminC as parameters, and (2) to known the best treatment. The researchwas use experimentaldesainwith 5 treatmentswereP0=without KMnO4,P1=0,6gKMnO4+absorber, P2=1,2g KMnO4+absorber,P3=1,8gKMnO4+absorber, dan P4=2,4g KMnO4+absorber and 4 repeatation. Datawas analized by Annova and DuncanTest at á=5%. The result showed that shelflife of guava treated by KMnO4was 8 dayswhilewithout KMnO4was 6days. Based on Annova at á=5%, KMnO4 treatment was significant on weight lose and hardnessparameters butwas not significant on soluble solid content and vitamin C parameters. The best treatment in thisresearchwas P4 (2,4g KMnO4+absorber).Keywords: ethylene,KMnO4, guava, shelflife